Community support and youth recovery: the mediating role of peer and parental disapproval - Kosgolla, Janaka; Smith, Douglas; Lee, Alex; Reinhart, Crystal; Jurinsky, Jordan (Frontiers in Adolescent Medicine, 2025)
IntroductionThe study examined whether community-level support for substance use disorder (SUD) services was associated with youth recovery status, and whether this relationship was transmitted by peer or parent disapproval of substance use.MethodsData were drawn from the 2022 Illinois Youth Survey and county-level metrics from the Recovery Ecosystem Index (REI) mapping project. The analyses focused on four key constructs: how wrong your parents feel it would be for you to use substances (parental disapproval), how wrong your peers feel it would be for you to use substances (peer disapproval), self-reported recovery status (recovery status), and community recovery capital. The latter reflects various community-level indicators, such as recovery meetings and supportive policy environments. Using structural equation modeling, we tested the direct and indirect effects of community recovery capital on recovery status.ResultsOur findings indicated that a stronger community support environment was associated with higher peer and parental disapproval. In turn, peer and parental disapproval predicted a greater likelihood of self-reported recovery. The direct path from the community recovery capital to recovery status was not significant, suggesting that the relationship operates primarily through these mediators. Notably, the indirect effects accounted for approximately 76% of the total effect.DiscussionSupporting recovery services and a recovery-oriented system of care, may influence the parents and peers closer to youth entering recovery. Future research should extend these models by exploring additional mediators and examining longitudinal patterns to better understand the causal mechanisms at work.